MPH734 : Health management / Faculty of Medicine - UiTM, Faculty of Medicine (Universiti Teknologi MARA (UiTM), 2021)
This is a three-unit course. This course will facilitate candidates with the appropriate health management knowledge in managing, analyzing and decision-making on various aspects when managing healthcare and healthcare related organizations. Candidates trained will have skills and be able to develop, assess, analyzed critically and make projections on the organization’s needs. Skills on identifying, analyzing, solving and evaluating health problems at the population base level will also be built-in among the graduates through this module.